New species of Calamus (Arecaceae; Calamoideae; Calaminae) from Sumatra - Henderson, Andrew; Rustiami, Himmah (Phytotaxa, 2019)
Seven new species of Calamus (Arecaceae; Calamoideae; Calaminae) from Sumatra are described and illustrated, and compared with similar species.